Cross-selling, switching costs and imperfect competition in British banks - Tianshu Zhao; Kent Matthews; Victor Murinde (Cardiff University, Cardiff Business School, 2011)
This paper attempts to evaluate the competitiveness of British banking in the presence of cross-selling and switching costs during 1993-2008. It presents estimates of a model of banking behaviour that encompasses switching costs as well as cross-selling of loans and offbalance sheet transactions. The evidence from panel estimation of the model lends support to our theoretical priors on the cross-selling behaviour of British banks, which helps explain the rapid growth of non-interest income during the last two decades. We also find that the consumer faced high switching costs in the loan market in the latter part of the sample period, as a result of lower competitiveness.
Keywords: G21; L13; 330